Engaged employees: The link between culturally aware leadership and effective knowledge management - Pramesti Wardani, Galuh; Ramaditya, Muhammad (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study analyzes the effect of cultural intelligence and knowledge-oriented leadership on knowledge management success with work engagement as a mediating variable at PT Bank DBS Indonesia, Jakarta's head office. This study uses a quantitative approach and cross-sectional design, with data collected through an online survey of 197 permanent and contract employees. The analysis technique used Structural Equation Modeling (SEM). The results showed that cultural intelligence and knowledge-oriented leadership have a positive and significant effect on knowledge management success. Work engagement acts as an important mediator in the relationship between these variables. These findings provide practical contributions for companies to improve knowledge management success through cross-cultural training, knowledge-oriented leadership, and strategies to increase work engagement. This research also extends the knowledge management literature in the context of multinational companies in Indonesia.